Effects of bovine lipid extract surfactant administration in preterm infants treated for respiratory distress syndrome. Issue 4 (24th March 2018) - Stockley, Elizabeth; Valotaire, Ronald; Miller, Michael; da Silva, Orlando
Abstract: Aim: To review the initial effectiveness of bovine lipid extract surfactant (BLES) for the treatment of respiratory distress syndrome in preterm infants. Methods and results: A retrospective review of data collected from infants born <37‐week gestation with respiratory distress syndrome treated with BLES between February 1, 2015 and March 1, 2016. Data were analyzed to determine the timing of initial dose, the length of time to wean the fraction of inspired oxygen (FiO2 ) concentration to 0.21 following initial dose, and the number of repeated doses given during hospital admission. Infants were subgrouped by gestational age stratum, 23 0 to 27 6  weeks (group 1), 28 0 to 31 6  weeks (group 2), and 32 0 to 36 6  weeks (group 3). Ninety‐eight infants received the surfactant during the study period. After applying exclusion criteria, 77 infants were analyzed. Mean (SD) gestational age was 28 (4) weeks, and mean (SD) birth weight was 1250 (602) g. Initial dose of BLES was given at a median (interquartile range) time of 29 (19‐43) minutes in group 1, 150 (20‐615) minutes in group 2, and 990 (53‐2025) minutes in group 3. Median (interquartile range) length of time to wean the FiO2 concentration to 0.21 was 14 (5‐56) minutes, 10 (5‐53) minutes, and 10 (5‐38) minutes in groups 1, 2, and 3, respectively. Ten infants required repeated doses. Conclusion: Given the rapid response of BLES in all the groups, careful monitoring of ventilator parameters is paramount to allow for rapid weaning and early extubation to avoid lung injury associated with mechanical ventilation. Abstract : Aim: To review the initial effectiveness of bovine lipid extract surfactant (BLES) for the treatment of respiratory distress syndrome in preterm infants. Methods and results: A retrospective review of data collected from infants born <37‐week gestation with respiratory distress syndrome treated with BLES between February 1, 2015 and March 1, 2016. Data were analyzed to determine the timing of initial dose, the length of time to wean the fraction of inspired oxygen (FiO2 ) concentration to 0.21 following initial dose, and the number of repeated doses given during hospital admission. Infants were subgrouped by gestational age stratum, 23 0 to 27 6  weeks (group 1), 28 0 to 31 6  weeks (group 2), and 32 0 to 36 6  weeks (group 3). Ninety‐eight infants received the surfactant during the study period. After applying exclusion criteria, 77 infants were analyzed. Mean (SD) gestational age was 28 (4) weeks, and mean (SD) birth weight was 1250 (602) g. Initial dose of BLES was given at a median (interquartile range) time of 29 (19‐43) minutes in group 1, 150 (20‐615) minutes in group 2, and 990 (53‐2025) minutes in group 3. Median (interquartile range) length of time to wean the FiO2 concentration to 0.21 was 14 (5‐56) minutes, 10 (5‐53) minutes, and 10 (5‐38) minutes in groups 1, 2, and 3, respectively. Ten infants required repeated doses. Conclusion: Given the rapid response of BLES in all the groups, careful monitoring of ventilator parameters is paramount to allow for rapid weaning and early extubation to avoid lung injury associated with mechanical ventilation.